Use of biomaterials in the surgical regenerative treatment of peri-implantitis: systematic review (Research, Society and Development, 2021)
The aim of this study was to review the scientific literature regarding the effectiveness of different biomaterials in the regenerative treatment of peri-implantitis. A systematic literature search was performed in PubMed/Medline, Web of Science, Science Direct, Embase, and the Cochrane Collaboration Library. Studies on the use of biomaterials in the regenerative treatment of peri-implantitis were selected. The search strategy retrieved 253 articles. After selection, six articles met all inclusion criteria and were included in the present systematic review. The studies showed that an initial therapeutic approach consisting of plaque control and implant surface decontamination and subsequent surgery for biomaterial placement were essential for the successful regenerative treatment of peri-implantitis defects. Analysis of all biomaterials used in surgical regenerative treatment showed that bovine bone grafts provided superior outcomes in terms of new bone formation compared to autogenous grafts and nanocrystalline hydroxyapatite. It is important to note that porous titanium granules have emerged as a promising biomaterial for the regenerative treatment of peri-implantitis. In conclusion, biomaterials are promising for the treatment of peri-implant bone defects and the number of in silico biomaterials that can provide treatment of excellence to patients with this condition is expected to increase in the near future.